2022
DOI: 10.3390/microorganisms10061239
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Holy Triangle of Quorum Sensing, Biofilm Formation, and Antibiotic Resistance in Pathogenic Bacteria

Abstract: Chronic and recurrent bacterial infections are frequently associated with the formation of biofilms on biotic or abiotic materials that are composed of mono- or multi-species cultures of bacteria/fungi embedded in an extracellular matrix produced by the microorganisms. Biofilm formation is, among others, regulated by quorum sensing (QS) which is an interbacterial communication system usually composed of two-component systems (TCSs) of secreted autoinducer compounds that activate signal transduction pathways th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 1,105 publications
0
59
0
1
Order By: Relevance
“…Quorum sensing also regulates the formation of biofilms such as the biofilm structure formation, dispersal of biofilm cells, and accumulation of biofilm biomass. It has also been suggested that auto-aggregation in the bacterial system may be promoted by quorum sensing ( Deng et al, 2020 , Sionov and Steinberg, 2022 ). Hence, the possible presence of anandamide in the T. claveryi methanolic and ethyl acetate extracts may explain the potent activity of these extracts on the biofilm of S. aureus IFO3060 ( Mukherjee and Bassler, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Quorum sensing also regulates the formation of biofilms such as the biofilm structure formation, dispersal of biofilm cells, and accumulation of biofilm biomass. It has also been suggested that auto-aggregation in the bacterial system may be promoted by quorum sensing ( Deng et al, 2020 , Sionov and Steinberg, 2022 ). Hence, the possible presence of anandamide in the T. claveryi methanolic and ethyl acetate extracts may explain the potent activity of these extracts on the biofilm of S. aureus IFO3060 ( Mukherjee and Bassler, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Virulence GacS-GacA (Francis et al, 2017), SagS (Petrova and Sauer, 2011), BfiS-BfiR (Petrova and Sauer, 2009), HptB-HsbR (Bhuwan et al, 2012), LadS (Chambonnier et al, 2016), RetS (Moscoso et al, 2011), RocS2-RocA2 (Sivaneson et al, 2011), RocS1-RocR-RocA1 (Kuchma et al, 2005), PvrS-PvrR (Mikkelsen et al, 2013), ChpA/PilG/PilH/ChpB (Inclan et al, 2016), FimS (AlgZ)-AlgR (Okkotsu et al, 2014), PhoQ-PhoP (McPhee et al, 2006), ColS-ColR (Francis et al, 2017), AgtS-AgtR (Francis et al, 2017), PprA-PprB (de Bentzmann et al, 2012), CbrA-CbrB (Yeung et al, 2011) BvgAS (Roy et al, 1989) Colonization of lower respiratory tract SagS (Petrova and Sauer, 2011), HptB-HsbR (Bhuwan et al, 2012;Chambonnier et al, 2016), RocS2-RocA2 (Sivaneson et al, 2011), RoxS-RoxR (Hurley et al, 2010) PlrSR (Bone et al, 2017) Intracellular survival GacS-GacA (Francis et al, 2017), RoxS-RoxR (Hurley et al, 2010), RisAS (Jungnitz et al, 1998) Acute/chronic switch GacS-GacA (Bhagirath et al, 2017), CpxA-CpxR (Tian et al, 2016), KinA-AlgB (Chand et al, 2011(Chand et al, , 2012 Quorum sensing dependent regulation GacS-GacA (Francis et al, 2017), PhoR-PhoB (Bielecki et al, 2015), ParS-ParR (Wang et al, 2013), CzcS-CzcR (Sionov and Steinberg, 2022) Unknown Biofilm formation and maintenance BfiS-BfiR (Petrova and Sauer, 2009), SagS (Petrova and Sauer, 2011), LadS …”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…Several phenotypes in bacteria are controlled by the QS system. These phenotypes range from basic cell mobility to more complex communal interactions including biofilm formation, production of virulence factors, modulation of metabolic activity, production of extracellular polymeric substance (EPS), acquisition of nutrients, competence of genetic material, resistance to antibiotics and the generation of secondary metabolites [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This enables the reception of information regarding population and cellular density in the immediate surroundings. The activation of the signal transduction pathways leads to adapted alterations in gene expression [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%